2020
DOI: 10.1055/s-0040-1709487
|View full text |Cite
|
Sign up to set email alerts
|

Donation after Circulatory Death: Potential Mechanisms of Injury and Preventative Strategies

Abstract: Donation after circulatory death (DCD) donors represent a potential means to help address the disparity between the number of patients awaiting liver transplantation (LT) and the availability of donor livers. While initial enthusiasm for DCD LT was high in the early 2000s, early reports of high rates of biliary complications and inferior graft survival resulted in reluctance among many transplant centers to use DCD liver grafts. As with all innovations in transplant practice, there is undoubtedly a learning cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…There is a strong correlation between factors such as the presence of warm ischemia-induced damage before cold ischemia during DCD (Donation after Circulatory Death) donor acquisition, blood stasis during warm ischemia, and microthrombosis of the microcirculation around the bile duct (17)(18)(19)(20). The national results of DCD LT are improving with the in-depth study of the mechanisms of DCD LT-related injuries and the practice of prevention strategies including improvement of procurement based (super rapid technique, minimizing warm ischemia time, and so on), minimizing cold ischemia time, machine perfusion, etc (21,22). In this study, 26 patients developed biliary complications during the follow-up period, with an overall incidence of 20.5%.…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong correlation between factors such as the presence of warm ischemia-induced damage before cold ischemia during DCD (Donation after Circulatory Death) donor acquisition, blood stasis during warm ischemia, and microthrombosis of the microcirculation around the bile duct (17)(18)(19)(20). The national results of DCD LT are improving with the in-depth study of the mechanisms of DCD LT-related injuries and the practice of prevention strategies including improvement of procurement based (super rapid technique, minimizing warm ischemia time, and so on), minimizing cold ischemia time, machine perfusion, etc (21,22). In this study, 26 patients developed biliary complications during the follow-up period, with an overall incidence of 20.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, for DCD liver recipients, it is necessary to minimize the complexity of the surgery and establish a more resilient environment for marginal grafts. This requires careful selection of recipients who can withstand the challenges of early allograft dysfunction (EAD) [99]. For high-risk donors, they need to be matched with low-risk recipients to shorten the CIT [100].…”
Section: Donor-recipient Matchingmentioning
confidence: 99%
“…Alternatively, the time from incision until cold perfusion of the organs is almost entirely within the procuring surgeons’ control. While both donor and recipient factors have been correlated with ischemic cholangiopathy (IC) following LT, previous studies have demonstrated that the time from donor asystole until cold perfusion/cross clamp is the most significant predictor of recipient outcome and the development of IC 4,5 . In those studies, on multivariate analysis, each minute increase in asystole‐cross clamp duration was associated with a 16% increase in odds for development of IC.…”
mentioning
confidence: 99%